1997
DOI: 10.1093/oxfordjournals.jbchem.a021726
|View full text |Cite
|
Sign up to set email alerts
|

Tissue and Subcellular Distributions, and Characterization of Rat Brain Protein Phosphatase 2A Containing a 72-kDa  /B'' Subunit

Abstract: A 74-kDa delta/B" subunit was isolated by heparin-Sepharose column chromatography from human erythrocyte protein phosphatase 2A (PP2A) consisting of a 34-kDa catalytic subunit (alpha/C) and 63- and 74-kDa regulatory subunits (beta/A and delta/B") in a ratio of 1:1:1. The purified delta/B" was used as an immunogen in mice, to prepare specific antisera against delta/B". Immunoblot analyses with the antisera detected an immunoreactive 72-kDa protein in the cytosol from various rat tissues including erythrocytes, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
20
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 0 publications
2
20
0
Order By: Relevance
“…Usui et al reported that the regulatory BЈ␦ subunit (or B56␦), originally purified from erythrocytes and named the BЉ (␦) subunit, is phosphorylated by PKA and that phosphorylated forms of BЈ␦ stimulate the catalytic activity of PP-2A in a substrate-specific manner (22,23). Immunoblot analysis using BЈ␦ antibody revealed that the level of expression of the protein was slightly higher in striatum than in neocortex (A.N., unpublished observations), the region in the central nervous system in which the level of expression of BЈ␦ was reported to be most abundant (24). BЈ␦ contains two consensus phosphorylation site motifs for PKA, and one or the other of these sites is also conserved in other B-type subunits, for example in B56␥3 (25).…”
Section: Discussionmentioning
confidence: 99%
“…Usui et al reported that the regulatory BЈ␦ subunit (or B56␦), originally purified from erythrocytes and named the BЉ (␦) subunit, is phosphorylated by PKA and that phosphorylated forms of BЈ␦ stimulate the catalytic activity of PP-2A in a substrate-specific manner (22,23). Immunoblot analysis using BЈ␦ antibody revealed that the level of expression of the protein was slightly higher in striatum than in neocortex (A.N., unpublished observations), the region in the central nervous system in which the level of expression of BЈ␦ was reported to be most abundant (24). BЈ␦ contains two consensus phosphorylation site motifs for PKA, and one or the other of these sites is also conserved in other B-type subunits, for example in B56␥3 (25).…”
Section: Discussionmentioning
confidence: 99%
“…22 Importantly, we have shown that in every case the mutation renders the A␣ subunit defective in binding B or C subunits, depending on whether the mutation is located in the N-terminal B subunit binding domain (repeats 1-10) or in the C-terminal C subunit binding region (repeats [11][12][13][14][15] (Fig. 1).…”
Section: Discussionmentioning
confidence: 99%
“…The A and C subunits both exist as 2 isoforms (␣ and ␤ ), whereas the B subunits fall into 3 families designated B, [2][3][4][5] , BЈ (also called B56) 6 -10 and BЉ. [11][12][13][14] A model demonstrating how the A, B and C subunits interact in the holoenzyme is shown in Figure 1. 15,16 The existence of so many regulatory subunits suggests that the various forms of PP2A have distinct functions.…”
mentioning
confidence: 99%
“…The B' family consists of numerous isoforms and splice variants whose molecular masses range from 54 to 68 kDa (Csortos et al, 1996;McCright et al, 1996;McCright and Virshup, 1995;Tanabe et al, 1996;Tehrani et al, 1996). The B'' family has at least four members, designated PR48 (Yan et al, 2000), PR59 (Voorhoeve et al, 1999), and PR72/PR130 (Hendrix et al, 1993;Nagase et al, 1997). PR72 and PR130 are splice variants of the same gene (Hendrix et al, 1993).…”
Section: Introductionmentioning
confidence: 99%